Large-Scale Survey of Unselected Automated Visual Fields in a Major Reading Center: Patterns and Data Analysis - Lilly Zborowski-Naveh; Rita Ehrlich; Moshe Luski; Dov Weinberger; Mona Boaz; Dan D. Gaton (Scientifica)
A prospective, randomized study was conducted to survey a large number of automated perimetry examinations in a central reading institute, obtaining practical information on unselected referred patients and their clinician “consumers”. Visual field records of 1041 patients were obtained, each evaluated by one of three glaucoma specialists. Statistical analysis was applied on demographics, physician characteristics, test reliability and visual field scores. Reliability was scored on a scale of 1 (excellent) to 5 (uninterpretable). Data from earlier examinations of these patients was also analyzed. The large majority of patients (70.4%) were referred due to glaucoma, ocular hypertension or suspected glaucoma. Most of the patients had threshold strategies: FastPac 24-2 or 30-2 (88.9%), Full Threshold (0.7%), and 10-2 (0.5%). In only 7 patients was short-wavelength automated perimetry (SWAP) performed. The Swedish Interactive Testing Algorithm (SITA) was applied in 1.0% of cases. More than half (56.8%) of the population had a reliability score of 1, and 22.7% had a score of 2, indicating a valid result for 79.4% of patients, providing clinically useful information. Linear regression analyses indicated that the Mean Defect was a better predictor of the visual field score than the Corrected Pattern Standard Deviation (CPSD), for the entire group and for each visual field score subgroup.